SUSTAINABLE DEVELOPMENT OF IMPLEMENTING QUALITY EDUCATION IN GHANA, WEST AFRICA THROUGH THE USE OF CAREER GUIDANCE MOBILE APPLICATION - Boampong, E. B. (Farabi Journal of Social Sciences, 2024)
This study explores the Ghanaian education career choice model by examining the career decisions of secondary school students. Utilizing field research, SWOT analysis, inspection, and market research, the study aims to offer recommendations for improving the Ghanaian educational system. The research spans articles published between 2000 and 2022. The study focuses on supporting secondary school students (ages 13–17) in developing their skills and finding fulfilling careers by providing necessary information and resources. The objective is to evaluate the Ghanaian educational system, identify challenges and limitations affecting its quality, and propose actionable recommendations to address these issues. Ghana’s educational landscape has evolved significantly since the pre-colonial era. Despite reforms aimed at enhancing the quality of life, the anticipated improvements in education quality remain elusive. The study highlights the potential of an intuitive mobile application for career guidance, enabling students to seek career advice, consult professional counselors, and persuade their parents to support their career choices. Findings on how the Ghanaian education system influences students’ career decisions are detailed. Keywords: Quality Education, secondary school students, adolescent age thirteen to seventeen, Ghana Education System. Information about the author: Boampong, Evans Bio – Master’s degree in Tourism of the Department of Recreational Geography and Tourism of the Faculty of Geography and Environmental Science, Al-Farabi Kazakh National University (Almaty, Kazakhstan, e-mail: evansboampong@gmail.com)